Ernesto Sabato Antes del fin: autobiographical thinking and care of the self - Urriago, Hernando (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The purpose of the article is to offer a reading of the book Antes  del fin, by Ernesto Sabato, cataloged as memoirs and, therefore, linked to the repertoire of autobiographical writings that were produced in Latin America at the end of the 20th century. For this we appeal to the notions of autobiographical thought, yo tejedor, self-care and parrhesia, allied to the theory of autobiography and the hermeneutics of the subject. We support the idea that far from the pessimism typical of melancholic old age, Sabato is encouraged by a hopeful attitude towards young people, whom he invites to fight for the preservation of utopia. With this we hope not only to highlight the importance of the autobiographical work of the Argentine writer, but also to open the possibility to study it based on the tradition of the Literature of the Self in Latin America that he helped to consolidate.